Internet-Based Cognitive Behavioral Therapy for Psychological Distress Associated With the COVID-19 Pandemic: A Pilot Randomized Controlled Trial - Aminoff, Victoria; Sellén, Malin; Sörliden, Elise; Ludvigsson, Mikael; Berg, Matilda; Andersson, Gerhard (Frontiers in Psychology, 2021)
Background: The COVID-19 pandemic has been associated with various negative psychological consequences. This is a challenge for society as regular psychological services cannot be offered to the same extent as before the pandemic. In addition to the requirement of social distancing there is a need to adjust psychological treatment components like exposure to avoid increasing the spread of the infection. Internet-delivered cognitive behaviour therapy (ICBT) has an established evidence base for a range of psychiatric problems and has been suggested as one possible approach to deal with the situation. The aim of this study was to conduct a randomized controlled pilot trial during the summer of 2020 with a broad focus on psychological distress and a treatment approach that tailors the intervention based on symptom profile and preferences. Methods: Following advertisement and interview we included 52 participants with elevated levels of psychological distress. They were randomly allocated to either seven week long individually tailored ICBT (n = 26) or to a wait-list control condition (n = 26). Measures of depression and quality of life were used as primary outcomes. We also included secondary outcome measures of anxiety, insomnia, trauma, stress, anger, and alcohol use. For screening we used the CoRonavIruS Health Impact Survey (CRISIS). Results: Overall moderate to large between-group effects were found at post-treatment in favour of the treatment on measures of both depression (BDI; Cohens d = 0.63; PHQ-9: d = 0.62) and anxiety (GAD-7; d = 0.82). This was also observed for stress symptoms (PSS-14; d = 1.04). No effects were seen on measures of quality of life, insomnia, symptoms of post-traumatic stress and anger. There was an effect on alcohol use (AUDIT; d = 0.54), which was not of clinical relevance. Conclusion: Individually tailored ICBT shows initial promise as a way to reduce psychological problems in association with the COVID-19 pandemic. A possible limitation was that the trial was conducted when the effects of the pandemic were decreasing and fewer people were affected by the restrictions (e.g., the summer of 2020).